Profitability of Trading Volume and Momentum in Jordanian Sub-indices - Gharaibeh, Omar (Jordan Journal of Business Administration, 2020)
The purpose of this paper is to examine whether there is a sub-index-level trading volume effect on expected returns. In addition, this paper addresses the role of trading volume in enhancing the momentum effect using the early-stage and late-stage strategies on Jordanian sub-indices. While the existence of trading volume effect and improving the momentum effect by trading volume have been investigated by previous research at the levels of individual stocks, industries and international market indices, this study is the first to investigate this role at the level of sub-indices. Using monthly data for all 23 Jordanian sub-indices from December 2009 until February 2017, this study found that trading volume is negatively related to expected return. Sub-indices with high (low) trading volume experience lower (higher) future returns over the next five years. The early-stage momentum strategy earns significant profits over the following five years, while the late-stage strategy achieves strong reversal starting in year 4. The findings show that past volume helps reconcile momentum effect “under reaction” and long-term contrarian “overreaction” effects. The CAPM of returns fails to explain the early-stage momentum strategy. These findings on sub-indices returns have important implications for academic researchers, practitioners and investors alike.